Brokering responsible research and innovation in in silico medicine - Elisa Elhadj; Zita Van Horenbeeck; Elisa Lievevrouw; Ine Van Hoyweghen (Journal of Responsible Innovation, 2024)
The implementation of Responsible Research and Innovation (RRI) in research projects has increased the need for interdisciplinary collaboration. This article presents our RRI approach within the Horizon 2020 ‘In Silico World' project, which aims to accelerate the adoption of in silico medicine through computer modeling and simulation tools in healthcare. To address the shortcomings of the ‘checklist approach' for integrating ethics and the risk of becoming checkboxes ourselves, we introduce the term ‘RRI brokers.’ It serves as a lens for evaluating the project's RRI activities and the dynamics that can be faced by Social Science and Humanities scholars (SSH), and as a means to acquire agency in our own positioning. We suggest that to strengthen RRI, more consideration is needed on how we present our expertise in these collaborations, and awareness of how we, as RRI brokers, move between translating, balancing, and shaping worlds, affecting what we broker and ourselves.